Teachers' COVID-19 awareness, distance learning education experiences and perceptions towards institutional readiness and challenges - Lapada, Aris Alea (Animo Repository, 2020)
Amidst the threat of COVID-19 pandemic in the Philippines, the educators, students, and the school are still coping and adjusting to the distance learning education. This study explored teachers' awareness about the COVID-19 pandemic and their opinion on their respective schools’ readiness, as well as their response to the challenges of conducting distance learning education in the Philippines. A validated questionnaire was developed to collect the relevant data for this study. The initial reliability test obtained 8.9 Cronbach’s alpha. Data gathering procedure was done through Google forms, which, after validation from the respective DepEd divisions and universities, were subsequently sent to the teachers via email. The results show that the teachers were highly aware of the presence and consequences caused by the COVID-19 pandemic. The correlation between teacher’s demographic profiles and awareness to COVID-19 shows no relationship at all. Nevertheless, the length of teaching experience and specialization is very strongly correlated to readiness to distance learning education. Simultaneously, the teachers’ geographic location is strongly correlated to readiness to adapt to distance learning education. Furthermore, only the teachers’ gender has a significant difference in their awareness of the COVID-19 pandemic. In contrast, teachers’ gender, length of teaching experience, and geographic location have significant differences with their readiness to distance learning education. This study can be used as a basis for further research particularly in developing institutional plans to better understand the status of their teachers and educational organizations, and schools’ readiness to teach and learn through distance learning approach; hence, preserving and continuing educational mission during the current or future pandemic as well as be prepared for any natural disasters.